Pengaruh Pengendalian Internal, Penerapan Standar Akuntansi Keuangan (SAK), Dan Bukti-Bukti (Kecukupan dan Kelayakan) Audit Terhadap Opini Laporan Keuangan Wajar Tanpa Pengecualian “Studi Penelitian Di Kantor Akuntan Publik Di Jakarta Selatan - Sanjaya, Rudi; Puji Rahayu, Lativa, Krida (LPPM University 17 Agustus 1945 Samarinda, 2021)
The purpose of this study was to determine the effect of internal control, the application of financial accounting standards (SAK), and audit evidence (adequacy and feasibility), either simultaneously or partially. The population used in this study are auditors who work at the Public Accounting Firm (KAP) located in South Jakarta. The sampling technique in this study used the purposive sampling method. This study uses primary data in the form of a questionnaire distributed at the public accounting firm in South Jakarta. Hypothesis testing in this study using multiple linear regression. The results show that the magnitude of the coefficient of determination is 0.535 or internal control, the application of financial accounting standards (SAK) and audit evidence (adequacy and feasibility) can explain the unqualified opinion on financial statements by 53.5%, while the rest (100%- 53.5% = 46.5%) is explained by other variables that are not used in the study such as limitations on audit scope, accounting systems and procedures, client survival factors, and company integrity, and the results of the hypothesis show that internal control, application of accounting standards Financial Statements (SAK), and audit evidence (Sufficiency and Eligibility) have a significant effect simultaneously or partially on the unqualified opinion on the financial statements.